Gallbladder Carcinoma Presenting With Elbow Swelling. (September 2020) - Pande, Shantanu S.; Goyal, Devendra; Chowdhury, Zachariah; Dhal, Ipsita; Kumar Singh, Abhishek
Abstract : Abstract: Common presentation of primary gallbladder carcinoma is with abdominal pain, or it may be detected incidentally in postcholecystectomy specimen for cholelithiasis. Primary gallbladder carcinoma spreads to adjacent hepatic parenchyma and locoregional nodes. Lung is a common extra-abdominal site, with other sites being relatively rare. We report a case of primary gallbladder carcinoma, which presented with elbow swelling in the absence of locoregional nodal spread detected on whole-body 18 F-FDG PET/contrast-enhanced CT at initial evaluation.